Pore Interconnectivity Analysis of Porous Three Dimensional Scaffolds of Poly (3-Hydroxybutyric Acid) (PHB) and Poly(3-Hydroxybutyric-co-3-Hydroxyvaleric Acid) (PHBV) Through Non-Invasive Color Staining Method - Saiful Irwan Zubairi; Mantalaris, Athanasios; Bismarck, Alexander (Universiti Kebangsaan Malaysia, 2015)
Polyhydroxyalkanoates (PHAs) has been investigated for more than eighty years. Ever since then, the scientists are kept on synthesizing and developing new polymers and application to suit human interests nowadays. The resourcefulness of PHAs has made them a good candidates for the study of their potential in a variety of areas from biomedical/medical fields to food, packaging, textile and household material. In medical field (specifically in tissue engineering application), producing a biocompatible 3-D scaffold with adaptable physical properties are essential. However, to the best of our knowledge, scaffolds from PHB and PHBV with thickness greater than 1 mm have not been produced yet. In this work, PHB and PHBV porous 3-D scaffolds with an improved thickness greater than 4 mm was fabricated using conventional method of solvent-casting particulate-leaching (SCPL). A preliminary assessment on the improved thickness 3-D scaffolds was carried out to examine its pore interconnectivity by using non-invasive color staining method. The vertical cross sections image of the stained scaffolds was analyzed by image analyzer software. This technique was considered simple, fast and cost effective method prior to the usage of super accurate analytical instruments (micro-computed tomography). The results showed that over 80% of the pores have been interconnected with the adjacent pores. Moreover, there was a good correlation between the predicted pore interconnectivity and porosity. These results indicated how well a simple technique can do by giving an overview of the internal morphology of a porous 3-D structure material.